Environmental policy with green consumerism - Ambec, Stefan,De Donder, Philippe (CESifo, Center for Economic Studies & Ifo Institute, 2020)
Is green consumerism beneficial to the environment and the economy? To shed light on this question, we study the political economy of environmental regulations in a model with neutral and green consumers where the latter derive some warm glow from buying a good of higher environmental quality produced by a profit-maximizing monopoly, while the good bought by neutral consumers is provided by a competitive fringe. Consumers unanimously vote for a standard set at a lower than first-best level, or for a tax delivering the first-best environmental protection level. Despite its under-provision of environmental protection, the standard dominates the tax from a welfare perspective due to its higher productive efficiency, i.e., a smaller gap between the environmental qualities of the two goods supplied. In stark contrast, voters unanimously prefer a tax to a standard when the willingness to pay for greener goods is small enough
10419/223529
Keywords: Graue Literatur; environmental regulation; corporate social responsibility; green consumerism; product differentiation; tax; standard; green label; political economy